THE EVALUATION OF CONTRIBUTION PINE RESIN TO THE COMMUNITY'S INCOME IN THE VILLAGE OF SENEREN PANTAN CUACA GAYO LUES DISTRICT - Ali Makmur (JURNAL HUTAN PULAU-PULAU KECIL, 2022)
The pine sap is one of the efforts to utilize natural resources, namely the wealth of forest products that can be used as a means to create jobs in order to provide added value to people's income. The purpose of this study was to determine the contribution of pine resin to community income in Seneren Village, Pantan Weather District, Gayo Lues Regency. The population in collecting research data was 20 pine resin tappers as respondents by conducting observations, direct interviews using questionnaires taken by Simple Random Sampling. The data analysis used in this research is qualitative and quantitative analysis. The results showed that the average income of pine sap tappers was IDR 7,625,000/respondent/month, income of other sectors was IDR 1,286,000 respondents/month and the total income of tappers was IDR 8,911,000 respondents/month, which contributed to community income or pine sap tappers reaching 85.57% respondent/month.